ETNOPEDAGOGI EGRANG BATOK DALAM PEMBELAJARAN PENDIDIKAN DASAR - Rudy Juli Saputra; Solehuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to examine the ethnopedagogy of coconut shell stilts as a traditional game-based learning model in elementary education. The background of this study is based on the decreasing physical play experience of children, the dominance of passive, gadget-based activities, and the suboptimal use of traditional games in Physical Education, Sports, and Health learning in elementary schools. In fact, traditional games have pedagogical potential in developing motor skills, creativity, collaboration, character, and cultural identity of students. Coconut shell stilts were chosen because they are simple, inexpensive, based on natural materials, and contain the values ​​of balance, courage, cooperation, sportsmanship, and love for local culture. This article uses a descriptive qualitative method with a conceptual study approach through literature review and analysis of learning model designs. Data were reviewed from literature on ethnopedagogy, traditional games, physical education, children's motor development, project-based learning, and character education. The results of the study indicate that coconut shell stilts can be developed into a one-semester learning model through the stages of cultural exploration, tool making, basic movement training, game variation development, class festivals, and authentic assessment. This model can develop gross motor skills, creativity, mutual cooperation, responsibility, sportsmanship, courage, and pride in local culture. Thus, stilt-based ethnopedagogy can be a contextual, affordable, inclusive, and meaningful learning alternative in elementary education.